A Tale of Two Royal Cities: The Narratives of Islamists' Intolerance in Yogyakarta and Solo - Muhammad Najib Azca; Hakimul Ikhwan; Mohammad Zaki Arrobi (Al-Jami'ah: Journal of Islamic Studies, 2019)
The article discusses the narratives of “Islamist” intolerance in two cities of Yogyakarta and Solo in the post-Suharto era. It aims to elucidate the multiplicity of intolerance acts and the complexity of underpinning factors to intolerance. It argues that Islamist intolerance has manifested in various forms, ranging from the ideological, instrumental, and symbolic form. However, these categorizations of ideological, instrumental, and symbolic are not clear-cut and permanent one, but there is always some possible overlap between them. There is also the possibility that the form of intolerance can change in different times and occasions. This study is based on fieldwork research taken during 2014-2016 in both cities. Methodologically, this research-based article used Extended Cased Method (ECM). The data was collected by employing indepth interview and participant observation with secondary sources such as local media and government documents.[Tulisan ini membahas narasi Islam intoleran di dua kota, Solo dan Yogyakarta, pasca rezim Soeharto. Selain itu juga menjelaskan sejumlah aksi intoleran dan kompleksitas faktor-faktor yang berkelindan dalam peristiwa tersebut. Tulisan ini mengajukan argumen bahwa Islam intoleran mempunyairagam bentuk, mulai dari ideologis, instrumentalis hingga simbolis. Meskipun demikian, kategori tersebut tidak bersifat kaku dan permanen, tetapi terkadang bersifat saling overlap satu sama lainnya. Ada kemungkinan juga bentuk intoleran berubah seiring dengan perubahan waktu dan kondisi. Kajian ini berdasarkan pada studi lapangan di dua kota pada rentang waktu 2014-2016. Secara metodologi kajian ini menggunakan pendekatan Extended Cased Method (ECM). Data dikumpulkan melalui serangkaian wawancara mendalam dan observasi partisipatif dengan didukung data sekunder dari arsip daerah dan sejumlah media surat kabar lokal.]